Antimycobacterial Activity of Solid Lipid Microparticles Loaded with Ursolic Acid and Oleanolic Acid: In Vitro, In Vivo, and Toxicity Assessments - Saini, Vinay; Mata Espinosa, Dulce; Pandey, Alok; Dighe, Vikas; Barrios Payán, Jorge; Prasad Myneedu, Vithal; Valdez Zarate, Ivan; Rajani, Dhanji P.; Anande, Lalit D.; Hernandez Pando, Rogelio; Srivastava, Rohit (Microorganisms (Basel), 2024)
Ursolic acid (UA) and oleanolic acid (OA) are hydrophobic triterpenoid isomers with demonstrated anti-mycobacterial (Mtb) and immune-regulatory properties, although their poor solubility limits clinical use. We report the development of solid lipid microparticles (SLMs) as delivery vehicles for UA and OA and evaluate their anti-Mtb efficacy in vitro and in vivo, as well as their acute toxicity. SLMs measured 0.7–0.89 µM in size, with complete in vitro release of OA and UA at 40 and 32 h, respectively. The minimum inhibitory concentration (MIC) of SLMs loaded with OA and UA was 40 µg/mL SLMs + 20 µg/mL OA + 20 µg/mL UA for drug-sensitive Mtb and 80 µg/mL SLMs + 40 µg/mL OA + 40 µg/mL UA for multidrug-resistant (MDR) Mtb. These SLMs showed an efficient reduction in Mtb burden in infected alveolar macrophages. In a murine model of late-stage progressive MDR-TB, aerosolized delivery of SLMs containing OA and UA via a metered-dose inhaler significantly reduced pulmonary bacterial loads and extended survival. In vivo, acute toxicity studies revealed no mortality or signs of toxicity. These findings demonstrate that SLMs are an optimal delivery system for terpenoids, providing potent in vitro and in vivo anti-TB activity with an excellent safety profile.